PERIPHERAL NEUROPATHY AMONG PATIENTS WITH TYPE 2 DIABETES USING MICHIGAN NEUROPATHY SCREENING INSTRUMENT - Hussain, Ahtar; Ahmad, Ibrar; Khan, Muhammad Nawaz; Zar, Adnan; Shahzad, Shahid (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the frequency of peripheral neuropathy and associated factors among patients with type 2 diabetes mellitus (T2DM), attending a tertiary care hospital via Michigan Neuropathy Screening Instrument (MNSI). Methodology: This cross-sectional study was conducted in the department of endocrinology and metabolic diseaes, Medical Teaching Institute, Lady Reading Hospital Peshawar, from March to December 2019. A total of 365 patients with T2DM were included in the study. All patients were evaluated for peripheral neuropathy using the two sets of MNSI (symptoms and examinations). Results: Mean age of the patients was 49.0±7.52 years. Mean body mass index (BMI) was 28.1±5.21 kg/m2, and mean glycated haemoglobin (HbA1c) was 10.1±1.56%. There wew 150 (41.10%) males and 215 (58.90) females. Based on the scoring of MNSI questionnaire, 239 (65.5%) had diabetic peripheral neuropathy (DPN) while using MNSI examination 252 (69.0%) had DPN. By combining both questionnaire and examination, DPN was present in 290 (79.5%) of the study participants. The factors associated with DPN after controlling for potential confounders were age of > 50, high levels of total cholesterol (TC) and low density lipoproteins (LDL). Conclusion: The frequency of DPN was found to be higher in our study population; the burden being high among males. Age, TC and LDL were found to have significant association.